SPAK Dependent Regulation of Peptide Transporters PEPT1 and PEPT2 - Jamshed Warsi; Luo Dong; Bernat Elvira; Madhuri S. Salker; Ekaterina Shumilina; Zohreh Hosseinzadeh; Florian Lang (Karger Publishers, 2014)
Background/Aims: SPAK (STE20-related proline/alanine-rich kinase) is a powerful regulator of renal tubular ion transport and blood pressure. Moreover, SPAK contributes to the regulation of cell volume. Little is known, however, about a role of SPAK in the regulation or organic solutes. The present study thus addressed the influence of SPAK on the peptide transporters PEPT1 and PEPT2. Methods: To this end, cRNA encoding PEPT1 or PEPT2 were injected into Xenopus laevis oocytes without or with additional injection of cRNA encoding wild-type, SPAK, WNK1 insensitive inactive T233ASPAK, constitutively active T233ESPAK, and catalytically inactive D212ASPAK. Electrogenic peptide (glycine-glycine) transport was determined by dual electrode voltage clamp and PEPT2 protein abundance in the cell membrane by chemiluminescence. Intestinal electrogenic peptide transport was estimated from peptide induced current in Ussing chamber experiments of jejunal segments isolated from gene targeted mice expressing SPAK resistant to WNK-dependent activation (spaktg/tg) and respective wild-type mice (spak+/+). Results: In PEPT1 and in PEPT2 expressing oocytes, but not in oocytes injected with water, the dipeptide gly-gly (2 mM) generated an inward current, which was significantly decreased following coexpression of SPAK. The effect of SPAK on PEPT1 was mimicked by T233ESPAK, but not by D212ASPAK or T233ASPAK. SPAK decreased maximal peptide induced current of PEPT1. Moreover, SPAK decreased carrier protein abundance in the cell membrane of PEPT2 expressing oocytes. In intestinal segments gly-gly generated a current, which was significantly higher in spaktg/tg than in spak+/+ mice. Conclusion: SPAK is a powerful regulator of peptide transporters PEPT1 and PEPT2.